Impact of Foreign Direct Investment in the Agricultural Sector on the Socio-Economic Development of Zambia Republic - Inna V. Andronova; Lubinda Haabazoka; Aaron Mwewa Kasonde (RUDN Journal of Economics)
Zambia is among the developing countries experiencing increasing poverty, declining productivity, and increasing dependence on raw materials such as copper, which is most affected by the volatility of global markets, and which has had a huge impact on the country’s level of economic prosperity. To address this problem, the Zambian Government has taken the path of promoting economic diversification, with agriculture being one of the most viable options due to its ability to create jobs, ensure food security and contribute to gross domestic product (GDP) by adding value and increasing output. The article examines the role that foreign direct investment in agriculture plays in the socio-economic development of Zambia. The identified competitive advantages prove that Zambia’s agricultural sector has significant investment potential, although the country does not have direct access to the sea. A study of incoming investment activity showed that tobacco production attracts the most investments to the country. A comparative analysis of the disadvantages and advantages of the Zambian agricultural sector conducted by the authors proves that the sector has the necessary elements of investment attractiveness.